Perancangan Pengalaman Pengguna Aplikasi SiKumuh sebagai Penataan Kawasan Kumuh Kota Bekasi berbasis Mobile menggunakan Metode Design Thinking - Tiar Adhi Bagaskara; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Bekasi City has a slum area of ​​443 Ha, but only 128.61 Ha has been successfully. The cause of a large number of slum areas is due to data and information that is not up to date concerning the spread of slum areas in every sub-district of Bekasi City. The lack of reports from the public regarding slum areas are one of the factors. Based on these problems, designing a mobile application user experience is necessary to facilitate people to report on slums easier. Data and information on slum conditions in every sub-district of Bekasi City will be up to date, and they can be handled immediately. This research uses the design thinking method, which consists of collecting user needs and problems by conducting interviews, analyzing problems and finding the right problems and needs, formulating solution ideas to determine solutions to problems and needs, making prototypes to design solutions form of application features, and usability testing to test aspects of effectiveness, efficiency, and satisfaction. Usability testing uses a task scenario to measure effectiveness and efficiency and a system usability scale (SUS) to measure satisfaction. A final usability score of 84.1 is obtained for those who had reported on slum areas, and it is included in group A (excellent). Meanwhile, a value of 78.5 was obtained for those who had never reported on slums, and this score is included in group B (good).